2018
DOI: 10.12965/jer.1836060.030
|View full text |Cite
|
Sign up to set email alerts
|

A study on the characteristics of standing posture of elderly women with sarcopenia in Korea

Abstract: This study intended to analyze the characteristics of standing posture and factors related to sarcopenia of elderly women in Korea to provide basic data for the development of rehabilitation programs designed to prevent and control of the sarcopenia of elderly women. A total of 194 elderly women, aged over 65 years old, living in Gyeonggi-do, were selected to diagnose the presence of sarcopenia through bioelectrical impedance analysis (BIA) and muscle function test (gait speed and grip strength). The subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“… 1 ) Alterations in postural alignment often occur to compensate for decreased muscle strength in older adults. 40 ) An incorrect body position negatively influences muscle function and can cause structural changes in overloaded parts of the spine, leading to pain, especially in older adults. 41 ) Additionally, back muscle function influences thoracic spinal compressive loading, which may contribute to the development of upper back pain.…”
Section: Discussionmentioning
confidence: 99%
“… 1 ) Alterations in postural alignment often occur to compensate for decreased muscle strength in older adults. 40 ) An incorrect body position negatively influences muscle function and can cause structural changes in overloaded parts of the spine, leading to pain, especially in older adults. 41 ) Additionally, back muscle function influences thoracic spinal compressive loading, which may contribute to the development of upper back pain.…”
Section: Discussionmentioning
confidence: 99%
“…Positioning the head in front of the body increases the sway of the center of gravity, which increases fatigue and impairs motor function [ 33 ]. Kim et al also found that patients with sarcopenia have ears and shoulders located more anteriorly than healthy people [ 34 ]. Therefore, standing posture may also be a risk factor for locomotive syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Percent body fat, segmental lean mass, and segmental fat mass were measured by bioelectrical impedance analysis (BIA) technique using 50 kHz Accuinq model BC360 (Kim et al, 2018;Yang et al, 2018). Circumference of body segment was collected using measuring tape, with the body height was measured using stadiometer.…”
Section: Instrumentationmentioning
confidence: 99%